Unexplained Illnesses Associated With a Subscription Meal Service, 2022 - Melanie J. Firestone; Craig W. Hedberg (Journal of Food Protection)
In recent years, shifting consumer demands have led to changes in the types of foods produced and how consumers obtain them. A growing demand for non–meat-based proteins has led to the development of new plant-based protein products. Simultaneously, there has been an increase in subscription-based meal services. In 2022, a subscription-based meal service, Daily Harvest, launched a new plant-based protein line of products called Crumbles. Shortly, thereafter, consumer complaints of gastrointestinal symptoms were heard, and Daily Harvest recalled the French Lentil and Leek Crumbles, which contained a unique ingredient, tara flour. We obtained case data from the Marler Clark law firm and conducted an epidemiologic investigation of the relationship between illness and consumption of food products distributed by Daily Harvest. We independently reviewed data on 338 people, including 264 people with supplemental food exposure information, and calculated minimal attack rates. Of 264 people who completed the supplemental survey, all (100%) consumed the Lentil and Leek Crumbles. Minimal attack rates were highest for the Lentil and Leek Crumbles (1.4%) followed by the Walnut and Thyme Crumbles (0.45%). Among 213 subscribers, the minimal attack rate was highest for those who purchased three or more units of Lentil and Leek Crumbles (3.72%) compared to those who purchased two units (2.28%) or one unit (1.50%). The strength of the association and the increased risk of illness among persons who consumed Lentil and Leek Crumbles, but not other products that shared ingredients (other than tara flour) with Lentil and Leek Crumbles, suggests that tara flour was likely the source of illness, although a specific etiology remains unknown. This study highlights the value of using nontraditional data to identify sources of illness. Further research is needed to understand the safety of tara flour for human consumption.